Implementasi Teknik Memirsa dalam Pembelajaran Cerpen Tukang Cukur Karya Budi Darma untuk Meningkatkan Pemahaman Siswa SMA Kelas XI - Haris Oktariansyah; Margareta Andriani; Nur Attikah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The Merdeka Learning Campus Merdeka Program, also known as MBKM, is an activity that provides students with the opportunity to learn outside the classroom, one of which is teaching assistance. This paper aims to describe the activities conducted by students of Universitas Bina Darma Palembang in community service by implementing learning through the viewing technique in the Indonesian language subject for 11th grade students in the Merdeka curriculum. Through learning with the viewing technique, it is expected that students will be able to answer, summarize, and understand the intrinsic and extrinsic elements of the short story Tukang Cukur by Budi Darma. This Community Service (PkM) activity was conducted in the form of learning, counseling, and training. The PkM activity took place at SMA Arinda Palembang with 20 students. The method used in this activity was qualitative descriptive with data collection techniques of observation, note-taking, and documentation. After conducting learning on the short story Tukang Cukur by Budi Darma with the viewing technique in the 11th grade IPA class at SMA Arinda Palembang, positive results were observed. The majority of students were able to understand the content of the story, answer questions correctly, and improve their critical thinking skills, as well as their appreciation for literary works.